Evaluasi UI (User Interface) dan UX (User Experience) Untuk Menganalisis Kepuasan Pengguna Pada XYZZ - Yusran Bin Acho; Agung Panji Sasmito; Deddy Rudhistiar (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the influence of User Interface (UI) and User Experience (UX) on user satisfaction of the Xyzz application among Generation Z in the Greater Malang area. This research employs a quantitative approach with an associative design, involving 130 respondents aged 17–30 who have used the application at least once. Data were collected through questionnaires and analyzed using multiple linear regression, preceded by instrument testing and classical assumption tests. The results indicate that both UI and UX have a positive and significant effect on user satisfaction, both partially and simultaneously. The coefficient of determination shows that a substantial proportion of the variance in user satisfaction can be explained by UI and UX, with UX emerging as the most dominant variable.